Rancang Bangun Sistem Irigasi Tetes untuk Budidaya Cabai (Capsicum Annum L.) dalam Greenhouse di Nagari Biaro, Kecamatan Ampek Angkek, Kabupaten Agam, Sumatera Barat - Eri Gas Ekaputra; Delvi Yanti; Deni Saputra; Fadli Irsyad (Balai Teknik Irigasi, 2016)
Chili plants (Capsicum Annum L.) requires the availability of water in sufficient quantities and timely. The situation can be achieved by the application of drip irrigation system. This is due to the system can set the amount and timing in accordance with the water requirements of chili plants. This research was conducted in Nagari Biaro, District Ampek Angkek, Agam regency which aims to design a drip irrigation system that is suitable and appropriate for chili cultivation in the greenhouse. In this study, observations were conducted to the evapotranspiration of chili (ETC), technical testing, and feasibility analysis of drip irrigation systems. Based on the research results, highest ETc of 2.16 mm/day was occurred in the period from the beginning of the generative phase, with an average discharge droplets of 137.685 mm3/sec, the system operated for 0.84 hours/day to meet the water needs of chili plants. However, by considering the three parameters of technical feasibility, the system is still not feasible because there was only one that fits the required value, namely the distribution efficiency (91.49%). The uniformity (76.97%) and irrigation efficiency (74.37%) have not yet reached the minimum required value of 90%, this is caused by differences in head and the length of each channel, thus the pressure on the line was not uniform which causing varied discharge droplets.